2022
DOI: 10.1155/2022/2037904
|View full text |Cite|
|
Sign up to set email alerts
|

Establishment of Difficult Caudal Epidural Blockade Prediction Model

Abstract: Background. We aimed to develop a predictive difficult caudal epidural blockade (pDCEB) model when ultrasound was not available and verified the role of ultrasound in difficult caudal epidural blockade (CEB). Methods. From October 2018 to March 2019, this study consisted of three phases. First, we prospectively enrolled 202 patients scheduled to undergo caudal epidural anesthesia and assessed risk factors by binary logistic regression to develop the predictive scoring system. Second, we enrolled 87 patients to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 39 publications
0
1
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%